Pengembangan Video Animasi Materi Gerak Benda Untuk Meningkatkan Kemampuan Berpikir Kreatif - Damaiyanti, Ade; Andriani, Dwi; Bunayya, Haikal Wafi; Ritonga, Susi Febriani (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to improve students' creative thinking skills in science subjects with material motion of objects through animated video media. The research method used is the R&D (Research and Development) approach. In this study, data collection techniques were used in the form of media and material expert validation as well as pretest and posttest. The results showed that there was a significant increase in student responses from the results of the pretest and posttest. The average value of the pretest is 60% and the average value of the post test is 81.53%. So it was concluded that the development of animated video media can improve students' creative thinking skills. Keyword: Animation Video Development, Creative Thingking Ability